Implementation Of Total Quality Management (TQM) At the Lovely Beauty Center Padang Clinic - Nadhira Rinanta; Hendri Andi Mesta (Devitara Innovations, 2024)
Objective from study is know Implementation Total Quality Management (TQM) in clinics Lovely Beauty Center Padang. Research used​ is study qualitative with method descriptive, with Informant study use technique purposive sampling, techniques collection data with observation, interview And documentation, Steps used data collection, data reduction, data presentation. Results in implementing Total Quality Management researcher uses 4 components like customer focus, cooperation​ team, training and education, as well exists engagement and empowerment employee. Clinic Lovely Beauty Centre implementing TQM focusing on customers that is serve customer with friendly and honest, Implementation TQM cooperation team at the Clinic Lovely Beauty Centre namely on things that are of a nature urgent just. Where are the employees requested For help work other fields that require, Clinic Lovely Beauty Centre implementing TQM education and training that is with conducting training and training seminars, and the lovely beauty clinic centre implement TQM engagement and empowerment employee on pickup decision.